Bodies becoming art: Using a Deleuzian approach to explore the bodies and health of gay men. (1st July 2022) - Joy, Phillip; Numer, Matthew; Kirk, Sara; Aston, Megan; Goldberg, Lisa; Rehman, Laurene
The ways gay men navigate socially constructed body tensions are explored through a post-structural lens. Nine self-identifying gay men in Canada used photovoice to create images that expressed their beliefs, values and practices about their bodies. Participants took part in semi-structured interviews to discuss the meanings of their images. Three discursive considerations were created from the analysis of both interviews and the photographs. Participants attempted to create bodies aligned with the dominant body ideals for gay men but, in doing so, often suffered from emotional harm that negatively shaped their health and well-being. Some participants, however, through the process of creating their bodies were able to find new connections and new understanding of their bodies. They were able to find new ways of being outside the rigid body ideals set before them. Through the post-structural lens of the research, participants' bodies can be conceptualized as bodies becoming art.